Combined effect of boundary layer recirculation factor and stable energy on local air quality in the Pearl River Delta over southern China. (3rd July 2018) - Li, Haowen; Wang, Baomin; Fang, Xingqin; Zhu, Wei; Fan, Qi; Liao, Zhiheng; Liu, Jian; Zhang, Asi; Fan, Shaojia
ABSTRACT: Atmospheric boundary layer (ABL) has a significant impact on the spatial and temporal distribution of air pollutants. In order to gain a better understanding of how ABL affects the variation of air pollutants, atmospheric boundary layer observations were performed at Sanshui in the Pearl River Delta (PRD) region over southern China during the winter of 2013. Two types of typical ABL status that could lead to air pollution were analyzed comparatively: weak vertical diffusion ability type (WVDAT) and weak horizontal transportation ability type (WHTAT). Results show that (1) WVDAT was featured by moderate wind speed, consistent wind direction, and thick inversion layer at 600 1000 m above ground level (AGL), and air pollutants were restricted in the low altitudes due to the stable atmospheric structure; (2) WHTAT was characterized by calm wind, varied wind direction, and shallow intense ground inversion layer, and air pollutants accumulated in locally because of strong recirculation in the low ABL; (3) recirculation factor (RF) and stable energy (SE) were proved to be good indicators for horizontal transportation ability and vertical diffusion ability of the atmosphere, respectively. Combined utilization of RF and SE can be very helpful in the evaluation of air pollution potential of the ABL. Implications : Air quality data from ground and meteorological data collected from radio sounding in Sanshui in the Pearl River Delta showed that local air quality was poor when wind reversal was pronounced or temperature stratification state was stable. The combination of horizontal and vertical transportation ability of the local atmosphere should be taken into consideration when evaluating local environmental bearing capacity for air pollution.